2023
DOI: 10.3389/fpsyg.2023.1129752
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interaction on the adoption of electric vehicles: Mediating role of experience value

Abstract: The widespread adoption of electric vehicles (EVs) largely depends on the acceptance of the public. Previous studies pay more attention to the factors affecting EV adoption from the customer perspective but lack the perspective of the interaction between sellers and customers. Based on a survey of 1,014 respondents in China, this work developed a research model analyzing the effect of interaction on the intention to purchase EVs and using experience value (EPV) as the mediating variable. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…First, the company's marketing endeavors have played a pivotal part in propelling the acceptance and prevalence of EVs. Tesla has systematically dismantled conventional skepticism by showcasing electric vehicles' remarkable capabilities and inherent advantages [14]. Via sleek design, high-performance metrics, and a focus on real-world applicability, Tesla has adeptly demonstrated that EVs can stand as compelling alternatives to traditional internal combustion engine cars.…”
Section: Impact Of Tesla's Marketing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…First, the company's marketing endeavors have played a pivotal part in propelling the acceptance and prevalence of EVs. Tesla has systematically dismantled conventional skepticism by showcasing electric vehicles' remarkable capabilities and inherent advantages [14]. Via sleek design, high-performance metrics, and a focus on real-world applicability, Tesla has adeptly demonstrated that EVs can stand as compelling alternatives to traditional internal combustion engine cars.…”
Section: Impact Of Tesla's Marketing Strategymentioning
confidence: 99%
“…Among the most enduring impacts of Tesla's marketing strategy resides in its unwavering emphasis on innovation and technological leadership. It introduced innovative features such as Autopilot, which offers autonomous driving capabilities, and pioneered the concept of over-the-air software updates [14]. Hence, Tesla has not merely redefined the traditional concept of an automobile but has also inscribed its commitment to pushing the boundaries of automotive technology into the collective consciousness.…”
Section: Impact Of Tesla's Marketing Strategymentioning
confidence: 99%